Presence of Coliforms and Fecal Coliforms in Fast Food Items of Local Restaurants and Fast Food Outlets of Dhaka City - Faruk, Mohammad Omar; Akhter, Marufa Zerin (Bangladesh Journal of Microbiology, 2012)
The Microbiological status of 50 fast food samples collected from middle class and lower middle class retail outlets of fast food shops and restaurants at New Market and Dhanmondi area of Dhaka city were assessed. Eighty four percent of the samples were found to be satisfactory and 16% of the samples were found to be unsafe for human consumption. Total coliform, fecal coliform, Salmonella spp, Staphylococcus aureus and fungal count in 12%, 8%, 16%, 14% and 14% samples respectively have crossed the recommended limits and were unsafe for human consumption. Bare-handed handling of foods and use of unsafe water for dish washing and hand washing by food handlers, keeping food for long time under lighting in display glass boxes with elevated temperatures and storage of uncooked and half cooked meat items side by side in the refrigerator were noticed to be the possible sources and causes of microbiological contamination of the fast food items. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11810 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 49-51